Comparative assessment of clinical peculiarities of severe cerebrocranial trauma in benign and mortal outcome - Pyatikop, Vladimir A.; Masalitin, Igor N. (Ukrainian Neurosurgical Journal, 2017)
The aim of the paper was to compare clinical peculiarities of severe cerebrocranial trauma in benign and mortal outcome. Materials and methods. The paper analyzed 299 case histories of patients with severe cerebrocranial trauma, treated in Neurosurgical Department of Kharkiv Regional Clinical hospital from 2010 to 2013. Results. The patients who died due to severe cerebrocranial trauma were found to be hospitalized in severe condition confirmed by indices of Glasgow Coma Scale, DRS and RTS, large pathological substrates, a great number of lesions of the brain and displacement of medial structures. Conclusions. Statistically significant predicators of mortal outcome are low indices of Glasgow Coma Scale and RTS during hospital admission as well as large pathological substrates, their number and localization, significant displacement of medial structures of the brain.